PENGARUH TERAPI AIR REBUSAN DAUN SALAM TERHADAP PERUBAHAN TEKANAN DARAH PADA PENDERITA HIPERENSI DI WILAYAH TEMPUREJO JUMAPOLO KARANGANYAR: PENGARUH TERAPI AIR REBUSAN DAUN SALAM TERHADAP PERUBAHAN TEKANAN DARAH PADA PENDERITA HIPERENSI DI WILAYAH TEMPUREJO JUMAPOLO KARANGANYAR - Aji, Prima Trisna; Sani, Fakhrudin Nasru (Viva Medika, 2021)
Hypertension is a degenerative disease characterized by increased arterial construction resulting in resistance to blood flow which will increase blood pressure against the walls of the blood vessels. Hypertension is a chronic chronic disease, hypertension can damage the heart, kidneys, brain and other organs, causing abnormalities and death. One of the hypertension treatments is by giving bay leaf decoction. This type of research is a quasi experiment. The sampling technique uses total sampling. The research sample was 40 people with hypertension in the Tempurejo Jumapolo Karanganyar area. Test data analysis using the Wilcoxon test analysis. The results showed; 1) the average systolic blood pressure before giving the boiled water was 176.75 mmHg and the diastolic blood pressure was 98.25 mmHg; 2) blood pressure after giving the boiled water of bay leaves an average systolic blood pressure of 155.50 mmHg and an average diastolic blood pressure of 86.12 mmHg; and 3) there is an effect of bay leaf boiled water therapy on blood pressure in hypertensive patients in the Tempurejo Jumapolo Karanganyar area, this is evident from the Wilcoxon test results obtained p value 0,000.